PENINGKATAN KEMAMPUAN MEMBACA ANAK MELALUI STIMULASI VISUAL - Lusi Elva Diana; Tuti Yana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Improving reading skills for children is needed as a basis for future children's learning. Problems that occur are the low interest of children in reading often occurs in the learning process. For this reason, we need Medtode Innovation and Learning Media in education. The use of Visual Media as a method of improving children's reading skills is one way. This writing will discuss the analysis of the impact and effectiveness of the use of Visual Media in improving children's learning abilities